2020
DOI: 10.1073/pnas.2009748117
|View full text |Cite
|
Sign up to set email alerts
|

Rapid onsets of warming events trigger mass mortality of coral reef fish

Abstract: Our study reveals a hitherto overlooked ecological threat of climate change. Studies of warming events in the ocean have typically focused on the events’ maximum temperature and duration as the cause of devastating disturbances in coral reefs, kelp forests, and rocky shores. In this study, however, we found that the rate of onset (Ronset), rather than the peak, was the likely trigger of mass mortality of coral reef fishes in the Red Sea. Following a steep rise in water temperature (4.2 °C in 2.5 d), thermally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 50 publications
(58 reference statements)
0
60
0
Order By: Relevance
“…A relationship between increasing water temperature and amoebic gill disease (AGD) prevalence has been noted in Atlantic salmon cultured in several countries, and Benedicenti et al ( 2019 ) showed that salmon reared at higher temperatures (10 vs. 15°C) had earlier infections and more severe parasite loads. Finally, Genin et al ( 2020 ) suggest that while heat waves (“warming events”) may not directly kill coral reef fish, bacterial infections that occur following these events can result in mass mortality events.…”
Section: Discussionmentioning
confidence: 99%
“…A relationship between increasing water temperature and amoebic gill disease (AGD) prevalence has been noted in Atlantic salmon cultured in several countries, and Benedicenti et al ( 2019 ) showed that salmon reared at higher temperatures (10 vs. 15°C) had earlier infections and more severe parasite loads. Finally, Genin et al ( 2020 ) suggest that while heat waves (“warming events”) may not directly kill coral reef fish, bacterial infections that occur following these events can result in mass mortality events.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, high mortalities of sticklebacks in a mesocosm experiment during a heat wave were attributed to massive proliferations of infections with parasites (Wegner et al., 2008). Recently, high mortality of fish in the Northern Red Sea was triggered by a rapid onset of warming and the spread of a bacterial infection ( Streptococcus iniea ; Genin et al., 2020). Thus, extreme warming events can have strong effects on infectious diseases in cold‐blooded vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…7), acclimation and evolutionary adaptation are the only possible strategies. Furthermore, for ectotherms living at the edge of their upper thermal limits, an increase in extreme temperatures may generate temperature peaks that exceed physiological limits and cause high mortality (5,(8)(9)(10). Although this is expected to cause strong selection toward higher upper thermal tolerance, it is largely unknown, particularly within vertebrates, whether and at what rate organisms may adapt by evolving their thermal limits (11)(12)(13)(14).…”
mentioning
confidence: 99%